System architecture of a mobile message transport system. (9th February 2007) - Gloss, Bernd
Many scenarios of beyond-3G mobile communications describe the integration of various access technologies into one system. Being always best connected under certain optimisation criteria will be a crucial point for network operators and mobile users and requires network changes of mobile devices at runtime, the so-called vertical handovers. For those, bandwidth fluctuations up to the order of one or two magnitudes, e.g., when changing from an IEEE 802.11 to a GPRS System, have to be expected, and applications have to cope with them in an user friendly way. Multi-modality and flexible data representations exploiting weights and semantic of transmitted data as means for making applications resource adaptive are currently under investigation. On top of that, device and system-wide adaptation control instances are needed to solve cross-layer and inter-application issues. This requires a rethinking of the classical communication paradigm of OSI-like protocol layering. In this paper, an overview on adaptation in communications is presented and an experimental framework providing system support for application adaptation and adaptation control is introduced as part of the discussion.